Effects of nitrogen source, rate and foliar application on some leaf mineral nutrient contents and yield of “Sinnari” sweet oranges (Citrus sinensis L.) in the River Nile State, Sudan - Mekki, Mohammed H.; Elamin, Osman M.; Elkashif, Mohamed E. (Gezira Journal of Agricultural Science, 2018)
Sweet orange production in the Sudan is characterized by low yield and poor fruit quality. This research was aimed at determining the effects of nitrogen source, rate and foliar application on some leaf mineral nutrient content and yield of “Sinnari” sweet oranges in  the River Nile State during 2010/11 and 2011/12. Nitrogen sources were urea (100%), sheep manure (SM) (100%), or a combination of them (50% each), beside Wuxal foliar fertilizer. Nitrogen rates were 0, 43 and 86 kg N/ha. Treatments were arranged in a randomized complete block design with three replicates and 2 trees/plot. Results showed that nitrogen sources and rates were effective in increasing leaf nitrogen content and the highest values were obtained by the application of 86 kg N/ha using urea (100%) or a combination of urea and sheep manure. Application of Wuxal foliar fertilizer resulted in a significant increase of Zn and Fe leaf contents and total yield. Nitrogen source had significant effects on yield components and total yield. The highest values were obtained by a combination of urea and sheep manure or 100% urea, and the lowest values were recorded for 100% sheep manure. Nitrogen rate of 86 kg N/ha resulted in the highest yield components and total yield. It is recommended to fertilize sweet orange trees in the River Nile State with a combination of urea and sheep manure at the rate of 86 kg N/ha (12.4 kg SM/tree and 0.5 kg urea/tree) in addition to Wuxal foliar fertilizer.